MIF interacts with CXCR7 to promote receptor internalization, ERK1/2 and ZAP‐70 signaling, and lymphocyte chemotaxis. Issue 11 (2nd July 2015) - Alampour‐Rajabi, Setareh; El Bounkari, Omar; Rot, Antal; Müller‐Newen, Gerhard; Bachelerie, Françoise; Gawaz, Meinrad; Weber, Christian; Schober, Andreas; Bernhagen, Jürgen
ABSTRACT: Macrophage migration‐inhibitory factor (MIF) is a pleiotropic cytokine with chemokine‐like functions and is a mediator in numerous inflammatory conditions. Depending on the context, MIF signals through 1 or more of its receptors cluster of differentiation (CD)74, CXC‐motif chemokine receptor (CXCR)2, and CXCR4. In addition, heteromeric receptor complexes have been identified. We characterized the atypical chemokine receptor CXCR7 as a novel receptor for MIF. MIF promoted human CXCR7 internalization up to 40%, peaking at 50‐400 nM and 30 min, but CXCR7 internalization by MIF was not dependent on CXCR4. Yet, by coimmunoprecipitation, fluorescence microscopy, and a proximity ligation assay, CXCR7 was found to engage in MIF receptor complexes with CXCR4 and CD74, both after ectopic overexpression and in endogenous conditions in a human B‐cell line. Receptor competition binding and coimmunoprecipitation studies combined with sulfo‐SBED‐biotintransfer provided evidence for a direct interaction between MIF and CXCR7. Finally, we demonstrated MIF/CXCR7‐mediated functional responses. Blockade of CXCR7 suppressed MIF‐mediated ERK‐ and zeta‐chain‐associated protein kinase (ZAP)‐70 activation (from 2.1‐ to 1.2‐fold and from 2.5‐ to 1.6‐fold, respectively) and fully abrogated primary murine B‐cell chemotaxis triggered by MIF, but not by CXCL12. B cells from Cxcr7 ‐/‐ mice exhibited an ablated transmigration response to MIF, indicating that CXCR7 is essential for MIF‐promoted B‐cell migration. Our findings provide biochemical and functional evidence that MIF is an alternative ligand of CXCR7 and suggest a functional role of the MIF‐CXCR7 axis in B‐lymphocyte migration.—Alampour‐Rajabi, S., El Bounkari, O., Rot, A., Müller‐Newen, G., Bachelerie, F., Gawaz, M., Weber, C., Schober, A., Bernhagen, J. MIF interacts with CXCR7 to promote receptor internalization, ERK1/2 and ZAP‐70 signaling, and lymphocyte chemotaxis. FASEB J. 29, 4497‐4511 (2015). www.fasebj.org